Integrating Qualitative and Quantitative Methods for Water Resources Carrying Capacity Ⅱ: Application - Du Xuanxuan; Wu Xia; Chen Jinming; Jiang Rucheng; Gu Shixiang; Cheng Gang; Mao Changshu (E3S Web of Conferences)
The study focused on the application of theory and methods of the distributed quantitative assessment model and the dynamic feedback qualitative assessment of water resources carrying capacity (WRCC). The WRCC over eight typical areas of longitudinal Ridge-gorge region and plateau basin of Yunnan were studied. Results show that the results by quantitative assessment were consistent with that by qualitative assessment and accords with the fact, suggesting that theory and methods of the distributed quantitative assessment model and the dynamic feedback qualitative assessment of WRCC were useful for the study of WRCC. Results by two evaluation method suggest that the eight typical areas were areas of water shortage, and the local water resources could not bear the development of society and economy. It would a bad condition of the WRCC from 2020 to 2030 in eight typical areas. What’s more, a worsening trend would happen gradually during the following twenty years, suggesting that conflict between water supply and water demand becoming much fierce day by day. However, with inerbasin water transfer, WRCC enhanced significantly in contrary to that without interbasin water transfer, and rising trend would happen in the period of 2012-2030. Water resources in Zhongdian area could bear the development society and economy completely in the future, and that in the other typical area could also satisfy the requirements for the development of society and economy. In order to ensure sustainable socio-economic development, the construction of interbasin water transfer projects was very necessarily.